Silver-functionalized silica aerogels and their application in the removal of iodine from aqueous environments - Asmussen, R. Matthew; Matyáš, Josef; Qafoku, Nikolla P.; Kruger, Albert A. (Journal of hazardous materials, 2019)
[Display omitted] •Silver-functionalized silica aerogel (AgAero) is novel material for iodine capture.•AgAero completely and fast removed I− from different aqueous environments.•AgAero exhibited a preferred removal of I− over Br− and Cl−.•AgAero was able to remove IO3- in DIW through reduction to I−. One of the key challenges for radioactive waste management is the efficient capture and immobilization of radioiodine, because of its radiotoxicity, high mobility in the environment, and long half-life (t1/2 = 1.57 × 107 years). Silver-functionalized silica aerogel (AgAero) represents a strong candidate for safe sequestration of radioiodine from various nuclear waste streams and subsurface environments. Batch sorption experiments up to 10 days long were carried out in oxic and anoxic conditions in both deionized water (DIW) and various Hanford Site Waste Treatment Plant (WTP) off-gas condensate simulants containing from 5 to 10 ppm of iodide (I−) or iodate (IO3−). Also tested was the selectivity of AgAero towards I− in the presence of other halide anions. AgAero exhibited fast and complete removal of I− from DIW, slower but complete removal of I− from WTP off-gas simulants, preferred removal of I− over Br− and Cl−, and it demonstrated ability to remove IO3− through reduction to I−.